Reducing greenhouse gas emissions in oil palm plantations using a life cycle assessment approach - Harimurti, Danang; Hariyadi, Hariyadi; Noor, Erliza (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The growth of palm oil plantation in Indonesia has increased rapidly. Behind that rapid growth of palm oil comodities, negative issues and problems have emerged such as operation of palm oil plantation are caused of enviroment damage and the increasing of Greenhouse gases (GHGs) emissions. This study aims to analyze GHG emissions caused by palm oil plantation activities and provide an alternative to reduce GHG emissions through the reuse of solid and liquid waste as a substitute for inorganic fertilizers. The method used is a life cycle assessment based on the ISO 14040 framework. This study found that the average of GHG’s emission was 0.08 TCO2e/TFFB/Year. Fertilizing activities contributes the large amount of emissions of 0.07 TCO2e/TFFB/Year. Solutions to reduce GHG’s emission with optimize the use of remains organic fertilizer from CPO production process which is utilize the liquid waste and empty fruit bunch. The results from calculation of liquid waste utilization as fertilizer can be potential to reduct the GHG’s emission which produce is 0.015 TCO2eq/T TBS or equivalent to 17.03 % mean a while the utilication of FFB can potentially decrease GHG’s emission by 0.029 TCO2eq/T TBS or equivalent to 33.98%. The optimization of liquid waste and FFB make a sigfnificant in terms of reduction GHG’s emission in palm oil plantation.